PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, KOMITMEN ORGANISASI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN” (Studi Pada PT. Telkom Semarang Unit Regional Operation Center) - Regita Verella Dea Rahayu, 15.05.51.0302; Indriyaningrum, Kis (Students' Journal of Economic and Management, 2019)
The purpose of this study was to determine the effect of Transformational Leadership Style, Organizational Commitment, and Job Satisfaction on Employee Performance at PT. Telkom Semarang Regional Operation Unit Center. This study also aims to jointly find out the effects of the three independent variables on the dependent variable, and to find out which variables are the most dominant influence among the three independent variables on the dependent variable. This type of research uses quantitative research, with a population of 88 employees. Data collection using questionnaires with census samples. Based on the calculation of SPSS 21 in this study shows that Transformational Leadership has a positive and significant effect on employee performance. Whereas the Organizational Commitment variable and Job Satisfaction variable have no significant effect on Employee Performance. The coefficient of determination obtained value of 0.273 which means that transformational leadership variables, organizational commitment and job satisfaction can explain employee performance by 27.3% and the remainder is influenced by other variables not explained in this study.